Risk factors for the development of postoperative delirium in pediatric intensive care patients - Meyburg, Jochen; Ritsert, Mona-Lisa; Haken, Rebecca von; Picardi, Susanne; Westhoff, Jens; Silver, Gabrielle; Traube, Chani (Pediatric critical care medicine, 2018)
OBJECTIVES: To determine and quantify risk factors for postoperative pediatric delirium. - DESIGN: Single-center prospective cohort study. - SETTING: Twenty-two bed PICU in a tertiary care academic medical center in Germany. - PATIENTS: All children admitted after major elective surgery (n = 93; 0-17 yr). - INTERVENTIONS: After awakening, children were screened for delirium using the Cornell Assessment of Pediatric Delirium bid over a period of 5 days. Demographic and clinical data were collected from the initiation of general anesthesia. - MEASUREMENTS AND MAIN RESULTS: A total of 61 patients (66%) were delirious. Younger children developed delirium more frequently, and the symptoms were more pronounced. The number of preceding operations did not influence the risk of delirium. Total IV anesthesia had a lower risk than inhalational anesthesia (p < 0.05). Duration of anesthesia was similar in all groups. Patients with delirium had a longer duration of mechanical ventilation in the PICU (p < 0.001). Significant differences in cumulative doses of various medications (e.g., sedatives, analgesics, and anticholinergics) were noted between groups; these differences were independent of disease severity. Invasive catheters and respiratory devices (p < 0.01) as well as infections (p < 0.001) increased risk of delirium. - CONCLUSIONS: A high prevalence of delirium was noted in the PICU, and several perioperative risk factors were identified. Our data may be a base for development of strategies to prevent and treat postoperative delirium in children.